Strategy for Increasing the Capacity of Pokdarwis in Developing Tourism Villages in Lamongan Regency - Masadah; Vicky Indarto Setyono (SIMFONI: Jurnal Sains dan Sosial Multidisipliner, 2025)
The development of tourist villages requires the active role of tourism awareness groups (Pokdarwis) as the main drivers at the village level. This study aims to analyze strategies for increasing the capacity of Pokdarwis in developing tourist villages in Lamongan Regency. The study used a qualitative approach with a case study method in several existing and developing tourist villages. Data were collected through in-depth interviews, participant observation, and documentation. The results of the study indicate that increasing the capacity of Pokdarwis can be done through three main strategies: (1) strengthening human resource competencies through intensive training and mentoring, (2) multi-stakeholder collaboration between the government, universities, tourism actors, and local communities, and (3) program innovation based on local potential to increase tourist attractions. This study contributes to the understanding of strategies for strengthening Pokdarwis so that they are able to manage tourist villages sustainably.